Trg žrtava fašizma or Trg hrvatskih velikana -Victims of Fascism Square or Great Men of Croatia Square. Renaming of places and streets in post-communist Croatia in the early 1990's - Piškorec, Velimir (2008)
After the Socialist Republic of Croatia, a constitutive part of the former Socialist Federal Republic of Yugoslavia, declared its independence in 1991, its people had to cope not only with a new capitalist economic system, but also with some unforeseen, even tragical political and social developments. The most conspicuous of them were a war against the Serbian dominated Yugoslav People's Army and rebelling Croatian Serbs, as well as the subsequent occupation of nearly a third of the Croatian territory by the latter from 1991 to 1995. Although the irritation of the Croats caused by these events can be featured as the pivotal factor of national homogeneity during this period, another important element of this new national identity were attempts made by the new state to distance itself from its own communist past within Tito's Ex-Yugoslavia. On a symbolic level they were undertaken primarily in form of the systematic renaming of places and streets whose names were reminiscent of the former regime. Renaming practices of this period were accompanied by public discussions in which the proposals made by the politicians in power were not always welcomed by ordinary people or activists with another ideological background. In order to illustrate the above mentioned practices, this paper will present an analysis of relevant legal documents, selected newspaper articles and a corpus of ethnographic interviews with politicians, activists and citizens who participated in initiatives and discussions related to the renaming of places and streets in Croatia in the early 1990's.
Projekt MZOS
Projekt MZOS
ENG